Transforming a school into a professional learning community : a comparative study between Finland and Greece - Papadakou, Christina (2018)
Professional Learning Communities (PLC) set in the core of the school students’ learning by highlighting the vital role of the human resources of the school and their collaborative practices. Originally, the PLC model is rooted in the business sector, within the model of Learning Organization. As applied in educational settings benefits student learning through mutual trust and substantial collaboration. The aim of this study was to explore and compare PLC practices in two primary schools, one in Finland and one in Greece. A qualitative ethnographical comparative approach has been followed. Data collection methods were field observations for 9 days, field notes, and photographs from each school and interviews with school personnel. An interpretive thematic analysis was performed to reveal the main themes, inductively and deductively. Results indicated that the PLC model could be detected within the Finnish school, whereas within the Greek primary school the model could not be detected. Suggestions for the Finnish school related to the development of the existing leadership practices are discussed, while recommendations related to the need for a paradigm shift within the Greek school are suggested.